NILAI-NILAI RELIGIUS DALAM NOVEL HAFALAN SHALAT DELISA KARYA TERE-LIYE - Herlina Boru Regar; Nurizzati Nurizzati; Hamidin Hamidin (Faculty of Languages and Arts, Universitas Negeri Padang, 2012)
This purposes of study to describe religious values that defined in actor behavior in novel Hafalan Shalat Delisa author by Tere-Liye. Some of religious values are faith, syariah, and moral. This research is qualitative with descriptive method and content technique analysis. Data in this research is religious values in Hafalan Shalat Delisa. The source of data is novel by Tere-Liye that is Hafalan Shalat Delisa, which had been published by Republika in Februari 2012. This research found that the main actor of Hafalan Shalat Delisa is six years old girl named Delisa, whose pretty, and clever. Religious values in this novel include: (1) faith, which are acknowledge one God, Allah SWT, believe in Allah’s words, and fear only to Allah SWT; (2) syariah that are pray (shalat), dzikir, say grace, and read Qur’an; and (3) moral that are moral to God in the kind of loving Allah SWT, moral to parent, moral to self as forgiveness and patience.